Comparison of the acute perceptual and blood pressure response to heavy load and light load blood flow restriction resistance exercise in anterior cruciate ligament reconstruction patients and non-injured populations. (September 2018) - Hughes, Luke; Paton, Bruce; Haddad, Fares; Rosenblatt, Benjamin; Gissane, Conor; Patterson, Stephen David
Abstract: Objectives: To compare the acute perceptual and blood pressure responses to: 1) light load blood flow restriction resistance exercise (BFR-RE) in non-injured individuals and anterior cruciate ligament reconstruction (ACLR) patients; and 2) light load BFR-RE and heavy load RE (HL-RE) in ACLR patients. Design: Between-subjects, partially-randomised. Methods: This study comprised 3 groups: non-injured BFR-RE (NI-BFR); ACLR patients BFR-RE (ACLR-BFR); ACLR patients HL-RE (ACLR-HL). NI-BFR and ACLR-BFR performed 4 sets (30, 15, 15, 15 reps, total = 75 reps, 30s inter-set rest) of unilateral leg press exercise at 30% 1RM with continuous BFR at 80% limb occlusive pressure. ACLR-HL performed 3 × 10 reps (Total = 30 reps, 30s inter-set rest) of unilateral leg press exercise at 70% 1RM. Perceived exertion (RPE), muscle pain, knee pain and pre- and 5-min post-exercise blood pressure were measured. Results: RPE was higher in ACLR-BFR compared to NI-BFR ( p < 0.05). Muscle pain was higher in NI-BFR and ACLR-BFR compared to ACLR-HL ( p < 0.05). Knee pain was lower in ACLR-BFR compared to ACLR-HL ( p < 0.01). There were no differences in blood pressure. Conclusion: These responses to BFR exercise may not limit application and favourably influence knee pain throughout ACLR rehabilitation training programmes. These findings can help inform practitioners' decisions to utilise this tool. Highlights: Perceptual responses to BFR exercise are greater in ACLR patients than non-injured populations. Perceptual response is similar between BFR and heavy load exercise. BFR exercise causes less knee pain than heavy load exercise. BFR exercise may not exacerbate post-exercise blood pressure response. Responses to BFR exercise may not limit its application in ACLR patients.